Adaptive isolation system combining low-friction sliding pendulum bearings and SMA-based gap dampers. (1st June 2020) - De Domenico, Dario; Gandelli, Emanuele; Quaglini, Virginio
Highlights: Adaptive isolation system combining low-friction CSSs and SMA gap dampers (SMAGDs). SMAGDs introduce stiffening and energy dissipation beyond a threshold displacement. Satisfactory energy dissipation, high re-centering capability and reduced displacement. Linear procedure for preliminary analysis and design of the system is proposed. Elimination of undesirable effects typical of high-friction CSSs at low-intensity earthquakes. Abstract: The flag-shaped hysteretic behavior of Shape Memory Alloys (SMAs) can be conveniently used for developing efficient isolation systems, providing energy dissipation without implying residual displacements. This work presents a base isolation layout that combines low-friction curved surface sliders (CSSs) with SMA gap dampers (SMAGDs). The proposed SMAGDs are formed by a group of SMA wires placed in parallel with the CSS isolation system and connected to it through a sliding pin and a slotted ring in order to accomplish the "gap damper" feature. Based on this installation configuration, SMAGDs introduce additional stiffening and energy dissipation to the isolation system only when the displacement of the CSS exceeds a certain threshold or gap displacement d gap, while not being engaged for lower displacements. Consequently, the system exhibits a phased behavior, meaning that its reaction force depends on the amplitude of the displacement. This is particularly convenient for limiting seismic displacements while avoiding at the same time undesirable effects such as high structural accelerations and poor re-centering capability exhibited by alternative systems at low-intensity excitations, e.g. systems based on high-friction CSSs or combinations of CSSs with traditional supplemental energy dissipation devices. The paper describes a preliminary design procedure and the evaluation of the seismic performance of the proposed CSS + SMGAGD system. A leading design parameter of the SMAGDs is the overall cross-sectional area of the SMA wires, which is designed here through a direct displacement based procedure, by introducing some reasonable assumptions for the definition of the linear equivalent mechanical properties of CSS, SMAGD and combined CSS + SMAGD system. This performance-oriented design procedure is aimed at achieving a target displacement demand of the combined CSS + SMAGD system under the maximum credible design earthquake. A parametric study comprising a variety of CSS and SMAGD properties reveals that the proposed isolation layout is suitable to limit the maximum displacement under ultimate limit state earthquakes, providing at the same time satisfactory energy dissipation along with high re-centering capability, and outperforms both low-friction CSSs and high-friction CSSs.